(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Pharmaceutical analysis plays a key role in the quality assurance and quality control of bulk drugs. A documented validation program offers a high level of confidence that an operation or facility will consistently deliver a product that satisfies a set standard. A premilast is an aphosphodiesterase-4 inhibitor used in the treatment of psoriasis. Objective: The main objective is to develop a simple, rapid, accurate, and economical spectrophotometric method for the determination of apremilast in bulk and its tablet dosage form as per ICH guidelines. Materials and Method: The estimation was carried out using HPLC-grade acetonitrile as a solvent and quantitation was achieved using a double-beam UV spectrophotometer at 230 nm. The present method was suitable for its intended purpose as prescribed in ICH Q2 guidelines. The analytical method was validated to determine the linearity, precision, accuracy, robustness, ruggedness, LOD, and LOQ of the method. Results: The λmax of apremilast in acetonitrile was found to be 230 nm. The drug has a correlation coefficient (r2) value of 0.999 and exhibits linearity in the concentration range of 2–10 μg/mL. The proposed method was applied to pharmaceutical formulation and % the amount of drug estimated 99% was found in good agreement with the label claim. The repeatability, intraday, and interday changes of accuracy were examined. The approach is considered exact if the percentage RSD value is <2. Conclusion: The above method was a rapid and cost-effective quality control tool for routine analysis of apremilast in bulk and in pharmaceutical dosage form. The method can be useful for the day-to-day routine analysis in the quality control departments of bulk and pharmaceutical formulations industries.